Current trends and future directions in environmental geochemistry research - Sarkar, Dibyendu; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2007)
Increasing population growth and rapid industrialization with passing time have augmented the rate of deterioration of the environment, which is having a clear negative impact on human and ecological health. Although considerable research is now being undertaken in critical areas such as global change, environmental quality, and ecological protection, more collaborative, inter-disciplinary research is needed in order to ensure long-term environmental sustainability. A thorough understanding of the geochemistry of the earth's intrinsic processes is needed to develop a comprehensive, holistic model for the protection of the environment to ensure long-term sustainability in a global scale. This chapter briefly discusses some of the more salient current trends in environmental geochemistry research and a few of the many potential future directions of research in this area, often in close collaboration with experts in other scientific disciplines and policy makers geared towards maintaining earth system sustainability.
Keywords: Environmental sustainability; Long-term sustainability; Environmental geochemistry